Micro-enterprise development initiatives and entrepreneurial competencies, innovativeness, and social capital in Malaysia. Issue 8 (16th November 2016) - Al Mamun, Abdullah; Muniady, Rajennd; Yukthamarani, Permarupan P.; Noor Raihani Binti, Zainol; Mohamad, Mohd Rosli
ABSTRACT: This article examines the effect of participation in development programmes designed for women micro-entrepreneurs on the development of entrepreneurial competencies, innovativeness, and social capital. The study employed a cross-sectional design and quasi-experimental approach, and collected data from 417 women micro-entrepreneurs in Malaysia. Findings reveal that the participants possess a significantly higher level of social capital, innovativeness, and entrepreneurial competencies. Development organisations should therefore focus on redesigning their policies and programmes to improve the breadth and depth of the development programmes that they offer, which ultimately lead to an improvement in the social-economic condition of low-income households in Malaysia.